2006
DOI: 10.1097/01.mlr.0000208017.18278.1a
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Physician Attitudes and Beliefs on Treatment Decisions

Abstract: Although the understanding of basic and clinical science remains fundamental, clinical guideline authors may want to consider the importance of physician attitudes and beliefs in determining translation of their guidelines into clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…Additionally, our findings corroborate research indicating that situational factors, such as clinical scenarios and the urgency of decision making, influence SDM [32]. Finally, studies have shown that physician attitudes and beliefs determine translation of guidelines into clinical practice [33]; we found similar results in our study regarding HU and BMT.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, our findings corroborate research indicating that situational factors, such as clinical scenarios and the urgency of decision making, influence SDM [32]. Finally, studies have shown that physician attitudes and beliefs determine translation of guidelines into clinical practice [33]; we found similar results in our study regarding HU and BMT.…”
Section: Discussionsupporting
confidence: 90%
“…Relatively few patients received lipid-lowering medication, and intensification of such medication was uncommon. As was shown in other studies, GPs may have several reservations for prescribing lipid-lowering medication, such as expecting very few benefits in older patients or in patients with near-goal lipid levels 34 35. Also, patients can be reluctant to take them.…”
Section: Discussionmentioning
confidence: 95%
“…studied the impact of physician attitudes and beliefs on treatment decisions for lipid therapy in high‐risk patients and found that patients whose physicians believed ‘close enough to goal is good enough’ had 47% lower odds of receiving increases in statin dose (odds ratio, 0.53; confidence interval, 0.34–0.82). In comparison, patients whose physicians believed ‘statins are effective’ had almost twice the odds of having a dose increase (19). Our findings were in contradiction to these; no correlation between attitudes and self‐stated use of the therapies was found.…”
Section: Discussionmentioning
confidence: 99%